2021
DOI: 10.1111/polp.12396
|View full text |Cite
|
Sign up to set email alerts
|

The “Isms” of Regional Integration: What Do Underlying Interstate Preferences Hold for the ECOWAS Union?

Abstract: As the world starts reopening following the lockdowns prompted by the COVID‐19 pandemic, regional collaborations and trade matters have resurfaced. While the Brexit (British exit from the EU) negotiations have dominated regional trade headlines, the fate of the African Continental Free Trade Agreement is also being rethought. In all these, however, the issue of regional integration, administration, and governance of treaties and policies remain contentious areas. Considering these concerns, this article draws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Perhaps Britain can reconnect to the Commonwealth by taking a leading role in defending the global order, rule of law, democracy, freedom, and political values [75]. The role of Britain is crucial given that the liberal international order is in deep trouble and there are red flags just about everywhere-from outbreaks of populism, outright trade wars and threats of war from Russia [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps Britain can reconnect to the Commonwealth by taking a leading role in defending the global order, rule of law, democracy, freedom, and political values [75]. The role of Britain is crucial given that the liberal international order is in deep trouble and there are red flags just about everywhere-from outbreaks of populism, outright trade wars and threats of war from Russia [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…This means integration, whether regional or international, can benefit countries in non-economic areas such as peace and security. But in any case, weak institutions and poor policies are likely to generate bungling results (Igwe, Ochinanwata & Madichie, 2021). During the ECOWAS summit on May 30, 1990, in Banjul, the Gambia, a five-member standing mediation committee (SMC) was established to look into disputes and conflicts in Liberia (ECOWAS Decision, 1992).…”
Section: Peace and Securitymentioning
confidence: 99%
“…For effective realization, the ECOWAS Conflict Prevention Framework Focal Point Directorates are expected to work on strategies for improving conflict prevention plans and enhance crossdepartment collaborations and inclusive capacity building. To a very marginal degree, it has been revealed that the institutionalization of a stable democracy is one of the biggest achievements of the ECOWAS, with the exception of the coup d'état in Mali in 2012, in which case a 72-hour ultimatum was given to perpetrators to relinquish power or face sanctions (Igwe, Ochinanwata & Madichie, 2021). This is arguable, as democratic governance in the member states is fraught with abuses and has not even generated life-changing impacts.…”
Section: Peace and Securitymentioning
confidence: 99%
“…On the one hand, Chinese immigrant entrepreneurs have been able to respond to opportunities and challenges in the host business environment in Africa (see Ndoro, Louw, & Kanyangale, 2019;Madichie & Hinson, 2015). The Lebanese on the other hand, have demonstrated an enviable level of "tenacity and risk," which has enabled them to shed the burden of foreignness, as shown by their entrepreneurial endeavors in West Africa (Walker, 2010;Madichie, 2005;Madichie, 2010;Ogunyankin, 2018;Igwe, Ochinanwata, & Madichie, 2020).…”
Section: Prior Studies In African Businessmentioning
confidence: 99%